Strategies to Help ESL Students Improve their Communicative Competence and Class Participation: A Study in a Middle School - Claudia Gómez Palacio (Asociación Colombiana de Profesores de Ingles, 2010)
This article examines a qualitative study carried out at a middle school in North Carolina, the United States of America. The main purpose of the study was to find effective strategies that teachers can use to help ESL students improve their speaking skills and class participation. Results indicated that both communicative and social strategies as well as exposure to independent reading help ESL students improve their communicative skills and class participation.